A case report of congenital leukemia – AML M0 - S Kumar, Sreelakshmi; A, Bindu; KK, Purushothaman (Indian Journal of Child Health, 2023)
Congenital leukemia (CL) refers to leukemia diagnosed at birth or within the 1st month of life. Incidence is reported to be 1 in 5 million. We report the case of a 22-day-old neonate, who presented to us with features of sepsis, with predominant blasts in the peripheral smear, and was subsequently detected to have CL. Although the etiology is unknown, the presence of leukemia at birth suggests possible intrauterine exposure to drugs or other toxins or the presence of genetic abnormalities. The course of CL is one of the rapid deterioration and death from hemorrhage and infection unless treated appropriately, with adequate chemo and radiotherapy. These neonates pose a huge challenge to treat due to their high mortality, owing to both the high risk of treatment-related mortality and disease relapse. Early diagnosis and prompt initiation of treatment are essential for a better prognosis.